Eksplorasi Respon Pasien Gangguan Jiwa setelah Mendapat Home Visite dari Petugas Kesehatan - Ekowati, Wahyu; Suryanto, (Jurusan Keperawatan FIKES UNSOED, 2011)
The success of treatment in cases of mental disorder should not be simply imposed on a psychiatric unit, especially when patients were treated at a mental hospital. But it should be followed up with monitoring of treatment when the patient has returned home and cared for by family. One of the important agenda for health workers in the psychiatric unit is to conduct home visits to patients with mental disorders when the patient has been allowed to go home. It can bring a positive impact on families as well as for patients who visited by the health officers. The study was conducted qualitatively with the aim to determine the perception of mental patients after getting home visit by health officers. Indepth interviews were conducted on 8 patients and were analyzed using Collaizzi analysis techniques. The study identified four themes: (1) there was a positive response of patients toward home visits by health officers, (2) needs for mental health information were identified, (3) there was an expectation of mental health services and (4) patient's negative thoughts were identified. Recommendations based on the results of this study is that a structured home visit programs should be appliedin each unit of mental health services,so the aim of psychiatric nursing interventions can be achieved optimally either in hospital or in the community. The family is also expected to enhance its function and continue to provide motivation and encouragement for patients so that patients can re-socialize and productive, return to normal for the field work.